Framework to design water-energy solutions based on community perceptions: Case study from a Caribbean coast community in Colombia. Issue 1 (1st January 2021) - Benavides-Castillo, Juliana Maria; Carmona-Parra, Jaime Alberto; Rojas, Natalia; Stansfield, Kim E.; Colmenares-Quintero, Juan Carlos; Colmenares-Quintero, Ramon Fernando
Abstract: The off-grid communities in Colombia are characterised by the diversity of their geography, socio-cultural contexts, and structures of the system. Despite their potential, the opportunities for access to energy and therefore other conditions to develop education, productivity, health, technological projects, and recreation are highly limited. Under those conditions, the implementation of projects with water and/or energy solutions based on renewable sources would bridge the gaps of isolation and social marginalisation that have detained the future of these communities for years. Projects around water and/or energy require the input of external stakeholders to communities, despite of the willingness to change their realities towards a better lifestyle. To achieve a common point of interests among stakeholders, the dialogues, the understanding of the community cosmovision and the ethical perspectives regarding the use of natural resources are needed. Furthermore, it is necessary to identify perceptions of confidence and risk of renewable energy projects within the community. To design water and/or energy solutions based on the abovementioned in a sustainable manner, the framework "Community, wAter-Renewable Energies, Diversity" CARED is being developed, for which the first phase in its implementation is presented. The process has been carried out in the Wayuu indigenous community "La Paz" located nearby Manaure in La Guajira state in the northeast of Colombia.